Into new depths: climate-driven habitat expansion of the endangered skate Dipturus chilensis (Chondrichthyes, Rajiformes) - Jaime A. Villafaña; Diego Almendras; Daniel González-Aragón; Felipe I. Torres; Francisco J. Concha; Ana B. Guzmán-Castellanos; Ignacio Contreras; Karina E. Buldrini; Pablo Oyanadel-Urbina; Carolina A. Sandoval; Benjamín Miranda; Gabriel Mazo; et al. (Marine Environmental Research, 2026)

High-resolution monitoring of oxidative potential in urban air: A FOX assay-based online approach - J.-J. Sauvain; A. Toto; N. Concha-Lozano; M. Marro; G. Suarez (Atmospheric Environment, 2026)

Maternal effects of gestating red deer Hinds on fetal body condition: influence of individual and social environmental features - Concha Mateos; Javier Pérez-González; Eva de la Peña; José M. Seoane; Susana Alarcos; Cristina B. Sánchez-Prieto; Juan Carranza (Behavioral Ecology and Sociobiology, 2026)
Maternal effects —non-genetic influences of the mother on her offspring phenotype— play a crucial role in shaping early development and fitness. In large mammals, these effects have been mostly studied in relation to maternal condition (e.g., age, body mass, dominance status) and environmental constrains, whereas the influence of social context has received far less attention. Moreover, fetuses are rarely used as direct indicators of maternal effects, despite providing valuable insights into prenatal investment before postnatal processes emerge. Using a cross-sectional dataset of over 1100 red deer ( Cervus elaphus ) mother-fetus pairs from multiple populations and years, we investigated how maternal, environmental, and social factors interact to shape fetal condition. We predicted that maternal age, condition, and early conception would enhance fetal development, whereas harsh weather would constrain it. Variations in population structure affecting the level of male-male competition allowed us to assess the influence of social environment. We found that fetal weight increased with maternal age and early conception date, particularly in males, highlighting advantages linked to maternal experience and condition. However, in populations with intense male-male competition, mothers produced lighter fetuses, especially adult and older mothers under unfavorable weather and in late gestation, suggesting a cost of social interactions with males on prenatal growth. Our findings reveal that maternal traits, ambient environment, and social factors jointly modulate maternal effects on fetal development, underscoring the value of fetal traits as indicators of maternal effects in mammals, and suggesting an unexpected potential negative effect of male intrasexual competition on maternal allocation in polygynous species.

Toward a monocot SynBio toolkit: assessing regulatory element performance and eudicot compatibility - David B. May; Alexander C. Pfotenhauer; Bryn L. Concha; Li Li; Samantha M. Jones; Stacee A. Harbison; Lana H. Martin; Lindsey A. Clark; Alessandro Occhialini; C. Neal Stewart; Scott C. Lenaghan (Plant Cell Reports, 2025)

From restriction to Openness: Reproduction and innovation in vegan eating practices - Isabel M. Aguilera Bornand; Carlo Nuñez Concha; Claudia Giacoman (International Journal of Gastronomy and Food Science, 2025)

Fosfomycin in bacteraemic urinary tract infection due to multidrug-resistant Escherichia coli : insights of post hoc DOOR analysis of the FOREST trial - Jesús Sojo-Dorado; Inmaculada López-Hernández; Belén Gutiérrez-Gutiérrez; Sandra De la Rosa-Riestra; Fernando Docobo-Pérez; Alicia Hernánez-Torres; Álvaro Pascual; Jesús Rodriguez-Baño; Esperanza Merino de Lucas; Laura Escolà-Vergé; Elena Bereciartua; Elisa García-Vázquez; et al. (Infectious Diseases, 2025)

Unveiling Macroecological Patterns of Elasmobranchs in the Eastern Pacific Ocean - Andrés F. Navia; Joanna Alfaro‐Shigueto; Jose Ágreda‐Arango; Elisa Areano; Cristopher Avalos‐Castillo; Joseph J. Bizzarro; Carlos Bustamante; Adriana Cevallos; Francisco J. Concha; Víctor H. Cruz‐Escalona; David A. Ebert; Mario Espinoza; et al. (Journal of Biogeography, 2025)
Aim To examine the species richness, distribution and macroecological patterns of elasmobranch assemblages across a broad latitudinal gradient in the Eastern Pacific Ocean (EPO). Location The study area encompasses the Pacific coast of the American continent, spanning from 65°N to 60°S, and extending from the coastline to approximately 1000 km offshore, encompassing the oceanic archipelagos. Taxon Elasmobranchs. Methods Utilising the established distribution ranges of 190 elasmobranch species (comprising 89 sharks and 101 rays), we assessed the richness and spatial distribution of these species across the EPO. Subsequently, three macroecological patterns were scrutinised: Rapoport's rule, the Mid Domain Effect with its association to Mean Sea Surface Temperature, and the correlation between body size and latitudinal distribution. Results The analysis of species richness along latitudinal gradients unveiled a bimodal pattern, reaching peaks between 30° to 20°N and 10°N to 5°S. A decline in species richness was observed from tropical to polar regions. Contrary to Rapoport's Rule, Stevens' and midpoint methods demonstrated higher geographic range values at lower latitudes, diminishing towards higher latitudes. Additionally, the mid‐domain effect model exhibited a robust correlation with the mean sea surface temperature. Exploring the interspecific relationship between body size and extent of occurrence, it was found that 29 out of 190 species are more susceptible to extinction. Main Conclusion Marine elasmobranchs of the EPO defy conventional latitudinal richness patterns and deviate from Rapoport's rule. Furthermore, our findings indicate a robust correlation between observed richness and both sea surface temperature and environmental heterogeneity. The proportion of species vulnerable to human or stochastic impacts potentially leading to extirpation in relation to their geographic range was low across the majority of examined provinces.

Cheese whey and dairy manure anaerobic co-digestion at psychrophilic conditions: Technical and environmental evaluation - Miguel Casallas-Ojeda; Ivan Cabeza; Nestor Sanchez; Diana M. Caicedo-Concha; Sergi Astals (Environmental Research, 2024)

A green approach for the automatic quantitative analysis of additives in plastic samples using in-tube extraction dynamic headspace sampling technique coupled to GC-MS/MS - Estefanía Concha-Graña; Carmen M. Moscoso-Pérez; Verónica Fernández-González; Purificación López-Mahía; Soledad Muniategui-Lorenzo (Analytica Chimica Acta, 2024)

Phenotypic features, transcriptomic signatures and genomic regions associated with body ellipticity in the flatfish Senegalese sole - Patricia Gayo; Concha Berbel; Josefa Gómez-Maldonado; M. Gonzalo Claros; Manuel Manchado (Aquaculture, 2024)

Dragon’s Blood: antioxidant properties for nutraceuticals and pharmaceuticals - Isabella S. A. Peres; Kiara A. O. Conceição; Larissa A. F. Silva; Nadia G. Khouri; Cristiana M. P. Yoshida; Viktor O. C. Concha; Massimo Lucarini; Alessandra Durazzo; Antonello Santini; Eliana B. Souto; Patricia Severino (Rendiconti Lincei. Scienze Fisiche e Naturali, 2023)
Plants are the source of a large spectrum of phytochemicals, and the combined and concerted action of biologically active compounds lead to the potential beneficial properties of each plant matrix. A great attention is being addressed over the years toward herbs and medicinal plants. Dragon’s Blood is a reddish resin oil extracted from Croton lechleri tree. It has been extensively used by indigenous cultures of the Amazon River since ancient times due to the beneficial nutraceutical and pharmaceutical properties. This perspective aims at providing a current framework on Dragon’s Blood with focus on antioxidant properties for nutraceuticals and pharmaceuticals in a novelty integrated and multidisciplinary manner, highlighting the current knowledge, the main research lines, and emerging strategies. A literature quantitative research analysis approach was applied as starting point. The literature search was carried out by means of the Scopus database; 365 documents have been retrieved in the year range from 1854 to 2021, and a total of 269 terms were identified. Among the top-recurring keywords appear: unclassified drug, nonhuman, plant extract/s, Dragon’s Blood, dracaena, Dragon Blood, chemistry, human, animal/s, plant resin. Source, chemical composition, potential nutraceutical, and therapeutical applications of Dragon’s Blood are discussed here. The anti-inflammatory, wound healing, antidiarrheals, anticancer, antirheumatic, antiseptic, and antioxidant activities identified in the Dragon’s Blood extracts can open novel perspectives for its use in food and pharmaceutical industries. While different bioactive compounds have already been identified in Dragon’s Blood extract, only a few studies can be found in literature.

Evidence of natural selection and dominance of SARS-CoV-2 variant Lambda (C.37) over variants of concern in Cusco, Peru - Maria Antonieta Quispe-Ricalde; Hugo G. Castelán-Sánchez; Pablo M. Meza-Rodríguez; Sonia Dávila-Ramos; José Luis Sierra; Ramón Batista-Garcia; Fátima Concha-Velasco; Sonia Flores Lucana; José De Santa Cruz; Víctor Zea; Marco Galarza; Omar Caceres-Rey; et al. (Archives of Virology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) lineage C.37 (Lambda) has spread rapidly in Peru and other Latin American countries. However, most studies in Peru have focused on Lima, the capital city, without knowing the dynamics of the spread of the variant in other departments. Cusco, Peru, is one of the most popular departments in the country for tourists, so the introduction of new variants of SARS-CoV-2 might occur despite closure of the borders. Therefore, in this work, we analyzed the variants circulating in Cusco. The aim of this work was to better understand the distribution of SARS-CoV-2 lineages circulating in Cusco and to characterize the genomes of these strains. To this end, 46 SARS-CoV-2 genomes from vaccinated and unvaccinated patients were sequenced in the first half of 2021. The genomes were analyzed using phylogenetic and natural selection methods. Phylogenetic trees from Cusco showed dominance of the Lambda lineage over the variants of concern (VOCs), and there was no clustering of variants by district. Natural selection analysis revealed mutations, mainly in the spike protein, at positions 75, 246, 247, 707, 769, and 1020. In addition, we found that unvaccinated patients accumulated more new mutations than did vaccinated patients, and these included the F101Y mutation in ORF7a, E419A in NSP3, a deletion in S (21,618-22,501), and a deletion in ORF3a (25,437-26,122).

Lessons for research, capacity development and policy in agroforestry for development - D. Callo-Concha; M. Denich; M. M. Ul Hassan; F. Place; D. A. Wardell (Agroforestry Systems, 2017)

Bridging science and development: lessons learnt from two decades of development research - D. Callo-Concha; M. Denich; J. P. A. Lamers; A. Schwachula; A.-K. Hornidge; A. Khamzina; C. Borgemeister (Agroforestry Systems, 2017)

Oxidative discolouration in whole-head and cut lettuce: biochemical and environmental influences on a complex phenotype and potential breeding strategies to improve shelf-life - Paul J. Hunter; Laura D. Atkinson; Laura Vickers; Stella Lignou; Maria Jose Oruna-Concha; David Pink; Paul Hand; Guy Barker; Carol Wagstaff; James M. Monaghan (Euphytica, 2017)
Lettuce discolouration is a key post-harvest trait. The major enzyme controlling oxidative discolouration has long been considered to be polyphenol oxidase (PPO) however, levels of PPO and subsequent development of discolouration symptoms have not always correlated. The predominance of a latent state of the enzyme in plant tissues combined with substrate activation and contemporaneous suicide inactivation mechanisms are considered as potential explanations for this phenomenon. Leaf tissue physical properties have been associated with subsequent discolouration and these may be influenced by variation in nutrient availability, especially excess nitrogen and head maturity at harvest. Mild calcium and irrigation stress has also been associated with a reduction in subsequent discolouration, although excess irrigation has been linked to increased discolouration potentially through leaf physical properties. These environmental factors, including high temperature and UV light intensities, often have impacts on levels of phenolic compounds linking the environmental responses to the biochemistry of the PPO pathway. Breeding strategies targeting the PAL and PPO pathway biochemistry and environmental response genes are discussed as a more cost-effective method of mitigating oxidative discolouration then either modified atmosphere packaging or post-harvest treatments, although current understanding of the biochemistry means that such programs are likely to be limited in nature and it is likely that they will need to be deployed alongside other methods for the foreseeable future.

The role of waterfowl and fishing gear on zebra mussel larvae dispersal - Filipe Banha; Irene Gimeno; Munia Lanao; Vincent Touya; Concha Durán; Miguel A. Peribáñez; Pedro M. Anastácio (Biological Invasions, 2016)

Induction of capsaicinoid accumulation in placental tissues of Capsicum chinense Jacq. requires primary ammonia assimilation - Wendy del R. Ancona-Escalante; Fray M. Baas-Espinola; Lizbeth A. Castro-Concha; Felipe A. Vázquez-Flota; Marcela Zamudio-Maya; María L. de Miranda-Ham (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Inoculum and disease dynamics of circular leaf spot of persimmon caused by Mycosphaerella nawae under semi-arid conditions - Antonio Vicent; Daniel D. M. Bassimba; Concha Hinarejos; Jose L. Mira (European Journal of Plant Pathology, 2012)

Biomedical application of fuzzy association rules for identifying breast cancer biomarkers - F. J. Lopez; M. Cuadros; C. Cano; A. Concha; A. Blanco (Medical & Biological Engineering & Computing, 2012)

Reproductive biology of Zearaja chilensis (Chondrichthyes: Rajidae) in the south‐east Pacific Ocean - C. Bustamante; C. Vargas‐Caro; M. C. Oddone; F. Concha; H. Flores; J. Lamilla; M. B. Bennett (Journal of Fish Biology, 2012)
Between 2000 and 2002, three artisanal landing sites were sampled in southern Chile, with data on population structure and reproductive development collected from 5477 yellownose skates Zearaja chilensis . Total length ( L T ) ranged from 33 to 158 cm for females and 34 to 155 cm for males. No sexual dimorphism was evident in disc size (length or width) or in L T – mass relationships. The smallest mature female was 95 cm L T and the size at which 50% were mature ( L T50 ) was 109 cm. Males matured between 80 and 90 cm L T with a L T50 of 88 cm. Although the largest Z . chilensis captured by the artisanal fishery was 155 cm L T , 89% of landings comprised relatively small, immature fish. This situation may compromise the stock integrity if intrinsic vulnerability and probable long‐life span of Z . chilensis are considered. Consequences for the survival of the species and possible signs of a fishery collapse must be reviewed by management authorities by consideration of both artisanal and industrial landings in Chile.

Egg capsules of the dusky catshark Bythaelurus canescens (Carcharhiniformes, Scyliorhinidae) from the south‐eastern Pacific Ocean - F. Concha; C. Bustamante; M. C. Oddone; S. Hernández; J. Lamilla (Journal of Fish Biology, 2010)
The external morphology of the egg capsule of Bythaelurus canescens and its fixation to the substratum are described. Bythaelurus canescens egg capsules are typically vase‐shaped, dorso‐ventrally flattened, pale yellow in colour when fresh and covered by 12–15 longitudinal ridges. The anterior border of the capsule is straight, whereas the posterior border is semicircular. Two horns bearing long, coiled tendrils arise from the anterior and posterior ends of the capsule. The presence of longitudinal ridges and long coiled tendrils at both anterior and posterior ends of the capsule readily distinguish these egg capsules from those of other chondrichthyans occurring in the south‐east Pacific Ocean.

Is zinniol a true phytotoxin? Evaluation of its activity at the cellular level against Tagetes erecta - Joaquín A. Qui; Lizbeth A. Castro-Concha; Karlina García-Sosa; María L. Miranda-Ham; Luis M. Peña-Rodríguez (Journal of General Plant Pathology, 2010)

Skimmiwallinin, an additional skimmiwallinol derivative from the cuticular wax of Cocos nucifera - Fabiola Escalante-Erosa; Germán Carnevali Fernández-Concha; Luis M. Peña-Rodríguez (Natural Product Research, 2009)

IL4 in the 5q31 context: association studies of type 1 diabetes and rheumatoid arthritis in the Spanish population - Concepción Nuñez; Jose Luis Santiago; Jezabel Varadé; Hermenegildo de la Calle; M. Ángeles Figueredo; Benjamín Fernandez-Gutierrez; Emilio G. de la Concha; Elena Urcelay; Alfonso Martínez (Immunogenetics, 2008)

Influence of the inducible nitric oxide synthase gene (NOS2A) on inflammatory bowel disease susceptibility - M. Carmen Martín; Alfonso Martinez; J. Luis Mendoza; Carlos Taxonera; Manuel Díaz-Rubio; Miguel Fernández-Arquero; Emilio G. de la Concha; Elena Urcelay (Immunogenetics, 2007)

Sardine (Sardina pilchardus) spawning seasonality in European waters of the northeast Atlantic - Yorgos Stratoudakis; Stephen Coombs; Ana Lago de Lanzós; Nicholas Halliday; Gersom Costas; Bruno Caneco; Concha Franco; David Conway; M. Begoña Santos; Alexandra Silva; Miguel Bernal (Marine Biology, 2007)

Challenges in Hip Joint Modeling for a Patient with Proximal Femoral Focal Deficiency - Frank L. Buczek; Marguerite Evanoff-Jurkovic; M. Cecilia Concha; Kevin M. Cooney (Annals of Biomedical Engineering, 2003)

Topotecan in the Treatment of Acquired Immunodeficiency Syndrome-Related Progressive Multifocal Leukoencephalopathy - W Royal III; B Dupont; D McGuire; L Chang; K Goodkin; T Ernst; MJ Post; D Fish; G Pailloux; H Poncelet; M Concha; L Apuzzo; et al. (Journal of NeuroVirology, 2003)

Evaluation of the internalization process of the fish pathogen Renibacterium salmoninarum in cultured fish cells - M. González; F. Sánchez; M. I. Concha; J. Figueroa; M. I. Montecinos; G. León (Journal of Fish Diseases, 1999)